2021
DOI: 10.1038/s41586-021-04117-7
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid immunity improves B cells and antibodies against SARS-CoV-2 variants

Abstract: S an ti , M as si mi li ano Fabbiani, Ilaria Rancan, Mario T um ba re ll o, F ra nc es ca Montagnani, Claudia S al a , E ma nuele Montomoli & Rino RappuoliThis is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
205
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(234 citation statements)
references
References 33 publications
26
205
2
1
Order By: Relevance
“…To assess validity of the provided information on infection and vaccination status, we performed ELISA testing for SARS-CoV-2 NCP and S1 antibodies (Figure 2A). These results confirmed prior evidence that patients vaccinated after natural infection achieved the highest S1 antibody levels followed by vaccinated, but uninfected individuals[35]. The lowest S1 antibody levels were detected in individuals after natural infection without subsequent vaccination and the few individuals that were neither previously infected, nor vaccinated.…”
Section: Resultssupporting
confidence: 89%
“…To assess validity of the provided information on infection and vaccination status, we performed ELISA testing for SARS-CoV-2 NCP and S1 antibodies (Figure 2A). These results confirmed prior evidence that patients vaccinated after natural infection achieved the highest S1 antibody levels followed by vaccinated, but uninfected individuals[35]. The lowest S1 antibody levels were detected in individuals after natural infection without subsequent vaccination and the few individuals that were neither previously infected, nor vaccinated.…”
Section: Resultssupporting
confidence: 89%
“…Andreano et al dissected the nature of the memory B cell and antibody response at the single-cell level using samples from five naïve and five convalescent individuals vaccinated with the BNT162b2 mRNA vaccine. Consistent with our data, they found that the B.1.351 (Beta) and B.1.1.248 (Gamma) variants escaped almost seventy percent of the three thousand antibodies tested, in contrast to the B.1.1.7 (Alpha) and B.1.617.2 (Delta) variants, of which a much smaller portion were unaffected [22].…”
Section: Discussionsupporting
confidence: 90%
“…Studies are at odds regarding this topic, with some claiming that breakthrough infections are more likely to occur due to viral escape from antibodies [11,12]; others have demonstrated that mRNA vaccines remain effective through limiting COVID-19 severity, hospitalization and deaths [13][14][15][16][17][18][19][20][21]. Recently, more studies are exploring the efficacy of the natural immune response to SARS-CoV-2 vs. the mRNA vaccine-elicited response [22][23][24][25]. Our most recent work confirmed that following a natural infection, neutralizing antibody (nAbs) titers generated during infection accompanied by vaccination are significantly better in function than those generated by vaccination alone [26].…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies of this IGHV1-58/IGKV3-20 public clonotype bind to the ridge region of SARS-CoV-2 RBD ( Figure 5A ), and can be robustly elicited by infection with antigenically distinct variants of SARS-CoV-2 [39, 47] and by vaccination [48, 49]. These antibodies are also able to potently neutralize multiple variants of concern (VOC) [9, 48, 50].…”
Section: Resultsmentioning
confidence: 99%